ANDREI MAKINE IZMEĐU RUSIJE I FRANCUSKE (Филолошки студии, 2019)
The paper analyses the novels of Andreï Makine, a contemporary Russian-born French writer. It focuses on the bicultural aspects of his, so called, Russian-French trilogy – Le Testament français (Dreams of My Russian Summers), Requiem pour l'Est (Requiem for a Lost Empire) and La Terre et le ciel de Jacques Dorme (The Earth and Sky of Jacques Dorme). The second part of the paper examines the intercultural elements in Makine's collection of essays about French culture – Cette France qu'on oublie d' aimer (This France we forgot how to love) as well as in his interviews. The paper also discusses the reception of Makine's novels in Russia and France and how the critics categorise his identity.